ANALYSIS OF MICROPOROSITY ON POROUS CARBON FROM GELATIN (KPG) USING N2 ADSORPTION-DESORPTION BY DUBININ–RADUSHKEVICH (D-R) MODEL - Maria Ulfa (UNIVERSITAS SEBELAS MARET (UNS), 2017)
Porous gelatin carbons (KPG) sample with micropores were synthesized from gelatin via templating method. This study analyzed microporosity using the Dubinin– Radushkevich (D-R) equation. The result shows that KPG sample has microporous type with empirical parameter n=2 which describing the homogeneous degree of KPG with the high order of micropore filling. D-R plot shows that the increasing the ratio of gelatin to SBA-15 led to the decreasing the microporosity of samples. However, this increases the size and pore volume due to the success of templating process.The result of TEM shows the carbon particle aggregation and FTIR result shows that carbon particle were dominated by the functional group of oxygen and hydrocarbon. The energy of adsorption range of 5-10 kJ/mol and a value of n=2 demonstrated that the adsorption of nitrogen on the porous gelatin carbon (KPG) physically occurred which is applicable to the next gas adsorption process.